Distribution and occurrence of the diatom community in Göksu Stream, Adiyaman, Turkey - Cetin, A. Kadri; Yildirim, Vesile (My University, 2007)
Distribution patterns of planktonic, epipelic, epilithic and epiphytic diatoms in Göksu Stream, Turkey are presented here. All diatoms were collected monthly from April 2003 to March 2004 at seven stations along Göksu Stream. We reported a total of 70 diatom taxa at all stations. Out of these 70 diatoms, Pinnularia interrupta was solely recorded in the plankton, and Navicula cuspidata in the epipelon. Surirella spiralis was merely recorded in the epiphyton. The remaining diatom taxa were observed in different habitats. It was concluded that although some diatom species were more abundant in one habitat than in the others, species composition of diatoms in the stream is not significantly different. © by PSP.
Keywords: Diatoms; Epilithic; Epipelic; Epiphytic; Planktonic